Meal for Two: Creating Mood and Characterization Through Cinematography - Malvin Hernanta Betekeneng (Institute of Research and Community Outreach - Petra Christian University, 2019)
This creative work is about the cinematography report from the screenplay meal for two by Satrio Haryanto. The story tells about two neighbors, a man and a woman, who lives next door but they do not know about each other personally. The woman realizes that the man attracted to her but she prefers to keep her distance, but after sometime, they get together since both shares the same secret. This creative work aims to portray the mood in order to create suspense, distance and closeness and to show the man’s paraphilia, the man’s curiosity, and the woman’s introversion. An in-depth analysis will be further developed to portray the mood. In order to support those elements, there are several techniques used such as low-key lighting, framing. These techniques are to help the cinematographer to convey the drama suspense genre. In addition, a detailed analysis will further explain different uses of camera work, lighting, and color in building the characterization in the whole movie. As a result, my work as a cinematographer will explain on how the mood and characterization on this film fits with the drama suspense genre. Keywords: cinematography, low-key lighting, camerawork, color, framing.